2011
DOI: 10.3389/fnhum.2011.00091
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Alpha Activity is Modulated in Response to the Observation of Pain in Others

Abstract: The perception–action account of empathy states that observation of another person's state automatically activates a similar state in the observer. It is still unclear in what way ongoing sensorimotor alpha oscillations are involved in this process. Although they have been repeatedly implicated in (biological) action observation and understanding communicative gestures, less is known about their role in vicarious pain observation. Their role is understood as providing a graded inhibition through functional inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
72
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 87 publications
13
72
3
1
Order By: Relevance
“…The findings are also compatible with previous E/MEG studies showing that early responses to others' pain can be observed within 200 ms following stimulus onset (Cheng et al, 2008;. In addition, our findings are in line with those from previous studies on the perception of others' pain that have shown activation in regions of the cingulate (Höfle et al, 2013) and sensorimotor (Cheng et al, 2008;Whitmarsh et al, 2011) cortices, as well as in posterior brain regions, including the FG (Höfle et al, 2013;Singer et al, 2004). Finally, similar to previous reports, we found a Bpain effect^also in the STG (Botvinick et al, 2005;Singer et al, 2004), a region associated with salience (Hayes, Hayes, & Mikedis, 2012;White, Joseph, Francis, & Liddle, 2010) and social information processing (Bernhardt & Singer, 2012), which was extended to the posterior insula, which is known to be associated with the sensory experience of pain (Peyron et al, 2000;Sabatini et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings are also compatible with previous E/MEG studies showing that early responses to others' pain can be observed within 200 ms following stimulus onset (Cheng et al, 2008;. In addition, our findings are in line with those from previous studies on the perception of others' pain that have shown activation in regions of the cingulate (Höfle et al, 2013) and sensorimotor (Cheng et al, 2008;Whitmarsh et al, 2011) cortices, as well as in posterior brain regions, including the FG (Höfle et al, 2013;Singer et al, 2004). Finally, similar to previous reports, we found a Bpain effect^also in the STG (Botvinick et al, 2005;Singer et al, 2004), a region associated with salience (Hayes, Hayes, & Mikedis, 2012;White, Joseph, Francis, & Liddle, 2010) and social information processing (Bernhardt & Singer, 2012), which was extended to the posterior insula, which is known to be associated with the sensory experience of pain (Peyron et al, 2000;Sabatini et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies of pain perception (Cheng et al, 2008;Whitmarsh et al, 2011) and the attention-drawing nature of survival-related stimuli (Bradley, 2009), we found a Bpain effect^in the control group marked by significantly greater alpha suppression in the painful than in the neutral condition in the PCC. This pattern, which may reflect enhanced evaluation of the more important stimulus (i.e., pain), was altered in the pain-exposed group, suggesting that prior exposure to severe pain in others is associated with alterations to the neural response to pain-related stimuli in specific brain areas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Alpha rhythm functions through inhibition; an alpha oscillatory increase reflects suppressed cortical reactivity whereas alpha oscillatory suppression indexes enhanced reactivity and cortical recruitment (for a review, Jensen and Mazaheri, 2010). Evidence highlights the role of alpha rhythms in supporting social functions (Whitmarsh et al, 2011), biological motion (Ulloa and Pineda, 2007), and inter-individual synchronized actions (Dumas et al, 2010). Furthermore, EEG research showed that OT regulates alpha rhythms during social processing, possibly via modulation of MNS (Perry et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%